Overexpression, purification and characterization of a heat-stable peroxisomal glutathione reductase from Oryza sativa involved in multifactorial abiotic stress tolerance - Pamela Chanda Roy; Deepak Kumar Ojha; Welka Sahu; Mohammad Khalid Al-Sadoon; K. Sony Reddy; Gopal Chowdhary (Journal of King Saud University: Science)
Abiotic stress is the major bottleneck in obtaining the full potential of a standing crop. Various strategies have been investigated to impart abiotic stress tolerance. In the agricultural field, the stress conditions do not act in isolation rather they act synergistically in combinations against the wellbeing of the crop. The combined impact of abiotic stress conditions has been referred to as stress matrix or stress combination. Here, we have proposed a probable candidate that could be instrumental in imparting tolerance against stress matrix or stress combination. The investigation was made on a peroxisome localized glutathione reductase (GR) enzyme from the economically significant crop Oryza sativa. The protein was expressed in the E. coli system, purified and characterized. The enzyme was found to be active even at an elevated temperature of 55℃, demonstrating its abiotic stress tolerance properties. Further, the gene expression studies showed it to be upregulated under salinity, dehydration, low and high temperature. The expression was also investigated under various stress combinations and it was observed that the level of GR mRNA was found to be higher in the case of combined stress treatment as compared to individual stress conditions suggesting an additive effect phenomenon. The results obtained here put this peroxisomal GR in the spotlight for imparting abiotic stress combinations studies.